THE IMPACT OF ROSEHIP OIL ON QUALITY OF RYE-WHEAT BREAD - Lapytska, Надія; Syza, Ольга; Gorodyska, Олена; Savchenko, Олеся; Rebenok, Євген (Biota. Human. Technology, 2022)
In the study, it was aimed to use rosehip oil for the quality improvement of rye-wheat bread, made by a single-phase method. Use 1% of the oil to total mass of flour has almost no effect on the quality of the product, however it has positive influence on porosity, specific volume and dimensional stability of bread. Adding 3…5% of rosehip oil allows to increase the indicators of porosity, specific volume and dimensional stability of ready products by 8.3...16.7%, 15.0...30.0% and 9.3...16.3 % respectively. Addition of 7% of rosehip oil as maximum amount, caused decreasing of given quality indicators to 5% addition of the oil addition, but still remain higher by 11.7%, 20.0% and 11.6% respectively compare to initial bread. To investigate the reason of such effect, tests for studying activity of the dough microflora and their impact on the gluten, on acidity accumulation during the ripening process, on falling number of wheat and rye flour and also on their mixture were conducted. Adding 3...7% of rosehip oil increase microflora activity of rye-wheat dough. Increasing amount of rosehip oil, significantly increase activity of lactic acid bacteria and dough-raising power. In this regard, the acid accumulation intensifies, which is a positive result but it’s does not explain decreasing quality of ready product when 7% of oil was added. It’s possible to explain quality decreasing of ready product because addition of 7% rosehip has impact on wheat gluten and on rye falling number, also on wheat rye mixture. It was found out that oil dosage causes significantly increase strength of gluten. Gluten extensibility decreases by 1.5 times, elasticity by 28.3% compared to the control sample. The amount of raw gluten also decreases by 45.5%. Rosehip oil has a similar effect on the “fall number” parameter. This is especially noticeable when studying a model system made of rye flour. The purpose of the article is investigation the impact which rose hip oil can made on the quality of rye-wheat bread made by a single-phase method. Methodology. Microbiological, physicochemical and organoleptic research methods were used during the work. Processing of the results was carried out using MC Excel databases. The scientific novelty. It was first time investigated possibility of using rosehip fruit oil to improve the quality of rye-wheat bread; established its effect on the activity of microflora of rye-wheat dough; studied the effect on quality indicators of rye, wheat flour and their mixture. Conclusions: it was found out that for improving the properties of rye-wheat bread made by a single-phase method, it is advisable to use rosehip fruit oil in the amount of 3...5% of the total mass of flour.